Hubungan Riwayat Kontak dengan Penderita TB Paru Dewasa dan Riwayat Imunisasi BCG dengan Kejadian TB Paru pada Anak RS Husada - Ernawati, Ernawati; Lestari, Wiwik (Jurnal Kesehatan Holistic, 2018)
The infant mortality rate caused by TB in Indonesia is 91,368 per year or 250 people everyday (Depkes RI, 2010). This study was conducted to obtain a description of the relationship history of contact with adult tuberculosis patients and history of BCG immunization with the incidence of Pulmonary TB in Children in Child Poly Room Husada Hospital. This research uses correlative descriptive method. The population in this study were all pediatric patients aged 6 months - 12 years old who went to the Husada Hospital Clinic of Central Jakarta Hospital in March 2015 - April 2015. The sample in this study were 41 people with accidental sampling sampling technique. The results showed that there was a significant correlation between contact with adult patients with the incidence of Pulmonary TB in children in Poli Anak Husada Hospital and no significant relationship between BCG immunization with the incidence of Pulmonary TB in children in Poli Anak Husada Hospital.